ANALYSIS OF YOUTUBE CONTENT ‘CHANNEL: MARHABAN ACADEMY’ IN IMPROVING MUFRODAT MASTERY - Syafni, Hafidhah; Nuzula, Alfiyah Firdausi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
YouTube content has become a significant factor with notable effects and impacts on society today, particularly in the realms of education and learning. This is also true for Arabic language learning, where various educational contents are available to enhance learners' proficiency. The purpose of this study is to explore the